Antimicrobial Activity of Calcium-Enriched Mixture Cement and Biodentine on Enterococcus faecalis: An in Vitro Study - Nourzadeh, Mahdieh; Amini, Arezu; Fakoor, Farzaneh; Asgary, Saeed (Iranian Endodontic Journal, 2019)
Introduction: The main cause of endodontic failure is residual bacteria in the root canal system. Enterococcus faecalis (E. faecalis) is the predominant species isolated from infected root canals. This study aims to compare the antibacterial activity of calcium-enriched mixture (CEM) cement and Biodentine as root canal filling materials on E. faecalis. Methods and Materials: Seventy extracted human single-rooted teeth were prepared and infected with E. faecalis for 24 h. Specimens were randomly divided into control or experimental groups; the later were filled with either CEM cement or Biodentine. Dentinal samples were collected after 7 and 30 days and transferred to test tubes. After incubation, the number of colony forming units (CFUs) were counted and analyzed using the Kruskal-Wallis test, followed by the Mann Whitney U test. The level of significance was set at 0.05. Results: The reduction in mean CFU level of E. faecalis was significantly more in the presence of CEM cement at both time intervals (P<0.001). Compared to the positive control, Biodentine significantly reduced the mean CFU level only after 30 days (P<0.01). Conclusion: Although both biomaterials exerted antibacterial activity against E. faecalis, the CEM cement had more antibacterial activity than Biodentine. Keywords: Antibacterial Agent; Biodentine; Calcium-Enriched Mixture Cement; CEM Cement; Endodontics